Urinary biomarkers of exposure to glycol ethers and chlorinated solvents during pregnancy: determinants of exposure and comparison with indirect methods of exposure assessment. Issue 1 (24th June 2011) - Garlantézec, Ronan; Multigner, Luc; Labat, Laurence; Bonvallot, Nathalie; Pulkkinen, Juha; Dananché, Brigitte; Monfort, Christine; Rouget, Florence; Cordier, Sylvaine
Abstract : Objectives: To describe urine levels of metabolites of glycol ethers and chlorinated solvents in a sample of pregnant women from the general population, to study their occupational and non-occupational determinants and to compare them with the results of indirect assessment methods of solvent exposure. Methods: A sample of 451 pregnant women was randomly selected from a general population cohort. At inclusion, the women in this sample completed a self-administered questionnaire about their social and medical characteristics, occupation and exposure to different products at work and in non-occupational activities. Occupational exposure to solvents was assessed from the woman's self-report and from a job-exposure matrix. Eight alkoxycarboxylic acids and trichloroacetic acid and trichloroethanol were measured with chromatography in urine samples collected at inclusion. Associations between metabolite levels and job titles, exposure to products used at work, and solvent exposure were studied. Results: The different glycol ether metabolites were detected in 5.3%–96.4% of the urine samples, trichloroacetic acid in 6.4% and trichloroethanol in 5.5%. Nurses had butoxyacetic acid and phenoxyacetic acid in their urine most often, whereas methoxyethoxyacetic acid was the most frequent among nursing aides. Among cleaners, ethoxyacetic acid and ethoxyethoxyacetic acid were the most frequent. The occupation of hairdresser was associated with urinary excretion of ethoxyacetic acid, ethoxyethoxyacetic acid, butoxyacetic acid and phenoxyacetic acid. Among the women classified as exposed to solvents, the agents identified most often were ethoxyacetic acid, ethoxy-ethoxyacetic acid, butoxyacetic acid, phenoxyacetic acid, trichloroacetic acid and trichloroethanol. Ethoxyethoxyacetic acid was the only metabolite associated with non-occupational exposure. Conclusions: Metabolites of glycol ethers and chlorinated solvents were present at low levels in the urine of pregnant women. Most metabolites were associated with occupational exposure.